PENERAPAN MODEL PEMBELAJARAN RECIPROCAL TEACHING UNTUK MENINGKATKAN SIKAP ILMIAH DAN HASIL BELAJAR BIOLOGI SISWA KELAS X3 DI SMAN 1 KELAYANG TAHUN AJARAN 2013/20142 - Sapeni, Dwi Nanda Indah Sapeni Nanda Indah Sapeni; ', Darmawati; Syafi’i, Wan Syafi’i (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The aim of this research was to improve scientific attitude and biology learning result of students class X3 at SMAN 1 Kelayang with the application of reciprocal teaching model academic year 2013/2014. This research was conducted  at SMAN 1 Kelayang class X3 on May until June 2014. This research was a classroom action research and collaborated with teacher of SMAN 1 Kelayang. Subject of this research was student class X3 that consist of 38 students (17 boys and 21 girls). The parameters of this research were scientific attitude and learning result. Scientific attitude consist of curiosity, careful, responsibility, collaboration, tolerance, critical and honesty. Learning result consist of reserve capacity, student thoroughtness and students’ product assessment. Instrument of this research consists of learning materials and data collecting instruments. Procedure of this research consist of planning, implementation, observation and reflection. Data analysis consist of scientific attitude, students’ learning result and skills. The result showed that the mean score of scientific attitude on 1st cycle was 81,12% (enough) and increased on 2nd cycle with the mean score was 90.41% (good). For reserve capacity, the mean score on 1st cycle was 81,36% (good) and increased on 2nd cycle with the mean score was 88,02% (good). For studnts’ thoroughness individually, the mean score was 84,21% (thorough) on 1st cycle and 100% (thorough) on 2nd cycle. Based on the result, it can be conclude that the application of reciprocal teaching model could improve scientific attitude and biology learning result of students class X3 at SMAN 1 Kelayang academic year 2013/2014. Key words:   Improve scientific attitude, reciprocal teaching model, biology learning result